Examining the role of new media in upholding good governance in a democratic system : is there nexus amid media and good governance? - Mamokhere, J. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
The paper aimed at examining the role of new media [internet] in upholding good governance and democracy in the South African new dispensation. In this 21st century and Fourth Industrial Revolution (4IR) era, the role of new media has become complex and biasness, which raises many questions, if their role is relevant in fostering good governance and democracy. It is commonly understood that democracy can generate good governance because academics agree with the idea that democracy is an essential part of good governance. The more transparent and accountable the public institutions are; the better the quality of the government is. This is the reason why many international development organizations promote good governance via the promotion of greater transparency, rule of law, and democratic accountability. In brief, new media plays the watchdog role for the governing system of a country. In this regards, the new media examine the government and on those involved in governance. Moreover, new media also promote policy-making as well as the decision-making process. The new media exposes policy failures and successes, maladministration, corruption, and scandals in the public and private sector. South African government has been bid to ensure good governance in the country since the democratic regime in 1994. The Constitution of the Republic of South Africa, 1996, makes provision for good governance through the adherence of constitutional principles enshrined in Chapter 10 of the Constitution of the Republic of South Africa, 1996. This paper adopted the qualitative research design in the form of documents review to uncover the fundamental role of new media in enhancing governance principles. It embraced the Media Ecology Theory (MET) developed by Marshall McLuhan (1964) which aims to comprehend the social impact of technology and communication. Through an extensive literature review, the results of the paper indicate that new media plays the role of a watch-dog in promoting good governance and democracy.
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Democracy; Good governance; Media ecology theory; New media; Democracy -- South Africa; Corporate governance -- South Africa; Digital media; Industrial revolution -- South Africa